2016
DOI: 10.20885/iustum.vol23.iss4.art4
|View full text |Cite
|
Sign up to set email alerts
|

Perilaku Menyimpang Praktik Bisnis Periklanan dalam Perspektif Hukum Pidana dan Penegakan Hukumnya

Abstract: This research is aimed to analyze the criteria and form of deviation behaviour in business practice of advertisement and the deviation behaviour in business practice in the perspective of criminal law and its legal enforcement. This is a normative legal research using the regulation approach and concept approach. The data was collected and analysed using the descriptive -qualitative method. The result of the research showed that first; there are two criteria to show the deviation behaviour: fact of material an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Law enforcement in violation of consumer protection laws about advertising should be undertaken. It is also asserted by Amrani (2016) under the society and law enforcement should be involved in advertising surveillance, because in their research found the fact that low community participation is still in supervising cases of violations Advertising Law No 8 year 1999 article 17 paragraph 1 concerning information content. This is because people are reluctant to deal with legal institutions, and are resigned to unlawful advertising cases.…”
Section: How Should the Ads Regulation Be?mentioning
confidence: 99%
“…Law enforcement in violation of consumer protection laws about advertising should be undertaken. It is also asserted by Amrani (2016) under the society and law enforcement should be involved in advertising surveillance, because in their research found the fact that low community participation is still in supervising cases of violations Advertising Law No 8 year 1999 article 17 paragraph 1 concerning information content. This is because people are reluctant to deal with legal institutions, and are resigned to unlawful advertising cases.…”
Section: How Should the Ads Regulation Be?mentioning
confidence: 99%